The Seed Proteome Web Portal - Galland, Marc; Job, Dominique; Rajjou, Loïc (Frontiers in Plant Science, 2012)
The Seed Proteome Web Portal (SPWP; http://www.seedproteome.com/) gives access to information both on quantitative seed proteomic data and on seed-related protocols. Firstly, the SPWP provides access to the 475 different Arabidopsis seed proteins annotated from 2 dimensional electrophoresis (2DE) maps. Quantitative data are available for each protein according to their accumulation profile during the germination process. These proteins can be retrieved either in list format or directly on scanned 2DE maps. These proteomic data reveal that 40% of seed proteins maintain a stable abundance over germination, up to radicle protrusion. During sensu stricto germination (24 h upon imbibition) about 50% of the proteins display quantitative variations, exhibiting an increased abundance (35%) or a decreasing abundance (15%). Moreover, during radicle protrusion (24 h to 48 h upon imbibition), 41% proteins display quantitative variations with an increased (23%) or a decreasing abundance (18%). In addition, an analysis of the seed proteome revealed the importance of protein post-translational modifications as demonstrated by the poor correlation (r2 = 0.29) between the theoretical (predicted from Arabidopsis genome) and the observed protein isoelectric points. Secondly, the SPWP is a relevant technical resource for protocols specifically dedicated to Arabidopsis seed proteome studies. Concerning 2D electrophoresis, the user can find efficient procedures for sample preparation, electrophoresis coupled with gel analysis and protein identification by mass spectrometry, which we have routinely used during the last 12 years. Particular applications such as the detection of oxidized proteins or de novo synthetized proteins radiolabeled by [35S]-methionine are also given in great details. Future developments of this portal will include proteomic data from studies such as dormancy release and protein turnover through de novo protein synthesis analyses during germination.